2021
DOI: 10.3390/pharmaceutics13071063
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Lipid-Based Nanoparticles for Codelivery of Anticancer Drugs and siRNA for Treatment of Non-Small Cell Lung Cancer with Different Level of Resistance and EGFR Mutations

Abstract: Resistance to chemotherapy, enhanced proliferation, invasion, angiogenesis, and metastasis (RPIAM) represent major obstacles that limit the efficacy of cancer treatment especially in advanced stages of cancer. Overcoming or suppressing RPIAM can dramatically improve the treatment outcome. Non-small cell lung cancer (NSCLC) is frequently diagnosed in an advanced stage and often possesses intrinsic resistance to chemotherapy accompanied by the fast development of acquired resistance during the treatment. Oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 86 publications
(132 reference statements)
0
15
0
Order By: Relevance
“…In this experiment, hyaluronic acid gadolinium trioxide nanoparticles (HA-Gd2O3-NPs) were synthesized by hyaluronic acid, passivation molecule, and gadolinium chloride. Compared with normal lung tissue cells with low expression of EGFR, these new nanoparticles can specifically target lung cancer cells with high expression of EGFR, and can also realize active targeting to tumor cells through surface modified ligands Accurate drug delivery [ 12 ]. HA-Gd2O3-NPs, as a drug carrier, specifically targets EGFR mutant NSCLC cells and efficiently releases loaded drugs, which provides a new method for EGFR mutant lung cancer patients to overcome the resistance of EGFR-TKI.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, hyaluronic acid gadolinium trioxide nanoparticles (HA-Gd2O3-NPs) were synthesized by hyaluronic acid, passivation molecule, and gadolinium chloride. Compared with normal lung tissue cells with low expression of EGFR, these new nanoparticles can specifically target lung cancer cells with high expression of EGFR, and can also realize active targeting to tumor cells through surface modified ligands Accurate drug delivery [ 12 ]. HA-Gd2O3-NPs, as a drug carrier, specifically targets EGFR mutant NSCLC cells and efficiently releases loaded drugs, which provides a new method for EGFR mutant lung cancer patients to overcome the resistance of EGFR-TKI.…”
Section: Introductionmentioning
confidence: 99%
“…However, anionic SiRNA was coupled with cationic lipid ‐DOTAP whose linker was exposed on the surface of the carrier. The results demonstrated that this multicomponent delivery system has much higher anticancer efficacy (5−10‐fold) than individual components applied separately, which depicts the strong detecting ability of the system (Majumder & Minko, 2021). Overall, anti‐EGFR Fab′ and EGF conjugated NLBCs can bind to human tumor cells receptor with high specificity and selectivity.…”
Section: Nlbcs and Targeting Moietiesmentioning
confidence: 90%
“…Fluorophore rhodamine, which acts as an imaging agent, was loaded into the lipid phase during the synthesis process of the nanoparticles. The images showed that the rhodamine-labeled nanoparticles containing anticancer drugs and siRNA penetrated the lung cancer cells and localized in the cytoplasm, indicating successful cellular uptake of nanoparticles ( Majumder and Minko, 2021 ).…”
Section: Required Nanotherapeutics Properties For An Efficient Deliverymentioning
confidence: 99%